As startups sergipanas : um estudo de caso do Caju Valley - Felizola, Matheus Pereira Mattos (2016)
Startups are small organizations with replicable models of bold and business, in the process of launching or low operating time, with high potential for scalability and focus turned to the activities of research and development of innovative ideas. The Chestnut Valley Startups is a movement started in 2012 in favor of strengthening the innovation ecosystem in the state of Sergipe. The overall objective of the study was to map and analyze research activities, development and innovation and requests for registration of trademarks and software programs for Startups Sergipe. In terms of methodology, the work is descriptive, qualitative and as a method was chosen the multiple case study (Yin, 2015). The study was divided into three phases. In the first phase with analysis of records in files, open interviews with participants Cashew Valley Group and the direct observation of meetings. In the second phase, structured interviews with 20 companies participating in the Chestnut Valley and participant observation group. In the third phase were conducted in depth interviews with ten entrepreneurs Startups cited by Chestnut Valley movement given 10 criteria proposed by the research. The investigated group consists of companies participating in the movement 'Chestnut Valley' started in 2012, whose mission is to be a digital environment, centralizing the Startups movement which every day becomes stronger in the state of Sergipe. It was observed in the analysis that entrepreneurs do research, but still find it difficult to develop innovative products in general do not realize the importance of registration of computer or patent registration programs, or have concern for the trademark registration and due to the problems management and by their own shortcomings in the innovation ecosystem in Sergipe have failed to gain scalability.